2019
DOI: 10.1186/s40425-019-0611-3
|View full text |Cite
|
Sign up to set email alerts
|

Gal9/Tim-3 expression level is higher in AML patients who fail chemotherapy

Abstract: Immune checkpoint pathways active in Acute Myeloid Leukemia (AML) patients, especially during the course of remission induction chemotherapy, have not been well studied. Although dominant in mediating T cell dysfunction in cancer, it is now well-accepted that interruption of PD-1/PD-L1 axes alone does not always completely restore T cell function, indicating the involvement of additional negative regulatory pathways, such as TIM-3/Gal-9, in promoting T cell exhaustion. Here, we characterized these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 27 publications
2
54
0
1
Order By: Relevance
“…Many factors including immunosuppressive cells, cytokines and chemokines contribute to drug resistance in the tumor microenvironment [6, 7]. Higher infiltration of regulatory T cells (Tregs) could be significantly correlated with resistance to antiangiogenic therapy in metastatic renal cell carcinoma [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many factors including immunosuppressive cells, cytokines and chemokines contribute to drug resistance in the tumor microenvironment [6, 7]. Higher infiltration of regulatory T cells (Tregs) could be significantly correlated with resistance to antiangiogenic therapy in metastatic renal cell carcinoma [8].…”
Section: Introductionmentioning
confidence: 99%
“…Another “non-classical” LSC biomarker is T-cell immunoglobulin and mucin 3 (TIM-3), that is highly expressed on LSCs but not expressed on healthy HSCs ( 498 ). It is correlated to a poor prognosis ( 420 ) and treatment failure ( 423 ). Stem cell properties of TIM-3 + cells were confirmed by engraftment in a xenograft mouse model ( 421 ).…”
Section: Cscs and Their Origin At Tumor Initiationmentioning
confidence: 99%
“…Several studies reported increased levels of PD-1 as well as multiple co-expressing inhibitor receptors (IRs) on CD8 + T cells of AML patients at diagnosis [18,19]. Longitudinal observation of changes in the IRs expression pattern indicate that PD-1 and Tim3, together with several other coinhibitory receptors, are increased in bone marrow CD8 + T cells in non-responders and reduced in responders post chemotherapy [2,36]. Our analysis of TCRβ sequences showed that TCRβ clonotypes in CD8 + PD-1 + populations were more oligoclonal than those in CD8 + PD-1 − T populations.…”
Section: Discussionmentioning
confidence: 99%